The state of Vitamin D in Iraqi Patients With Parkinson Disease - Hatem, Aqeel Kareem (AL-Kindy College Medical Journal, 2019)
Background: A role for vitamin D deficiency in Parkinson disease (PD) has recently been suggested. Objective:: To estimate the state of vitamin D in PD with an age-matched healthy control. Type of the study: A case control study. Method: The study randomly comparison of plasma 25-hydroxyvitamin D (25[OH] D) concentrations of collected samples in a clinical neurology department ward / Baghdad teaching hospital / Medical City and Parkinson disease movement disorder clinic. Participants were registered into the study from October 2015 to October 2016. We was study serum vitamin D level in 40 consecutive patients with Parkinson disease and 40 age-matched healthy controls after matching for age, sex, race, and geographic location. Occurrence of suboptimal vitamin D 25(OH) concentrations in Parkinson patients. Results: Significantly, more patients with PD (62.5%) had deficient vitamin D than did controls (27.5%). The mean 25(OH) D concentration in PD was (18.09) significantly lower than in the control (24.89).. Conclusions: This study demonstrates a significantly lower vitamin D level in PD than healthy controls. These data support a possible role of vitamin D deficiency in PD.